Falling short : the bildungsroman and the crisis of self-fashioning - Stević, Aleksandar (Charlottesville : University of Virginia Press, 2020)
"This book examines the defining role of failure and inaction in the history of the bildungsroman in nineteenth- to early twentieth-century Europe"--
Introduction: On Taking Failure Seriously -- Lucien de Rubempré and the Politics of Usurpation in Post-Napoleonic France -- The Great Evasion: Dickensian Bildungsroman and the Logic of Dependency -- Charlotte Brontë and the Governess as a Liberal Subject -- Portrait of the Hero as an Ideologue, ca. 1885-1914 -- Madame de Guermantes and Other Animals: Proust and the Forms of Pleasure -- Epilogue: Historicizing the Bildungsroman.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on April 15, 2020).
eBooks on EBSCOhost
Keywords: Bildungsromans -- History and criticism; European literature -- History and criticism; Failure (Psychology) in literature; Maturation (Psychology) in literature; Self-realization in literature; Littérature européenne -- Histoire et critique; Échec dans la littérature.; Maturation (Psychologie) dans la littérature.; Réalisation de soi dans la littérature.; LITERARY CRITICISM / Semiotics & Theory; Bildungsromans; European literature; Failure (Psychology) in literature; Maturation (Psychology) in literature; Self-realization in literature; Criticism, interpretation, etc